Deteksi Dini Tumbuh Kembang Anak Usia Pra Sekolah di TKIT Yarsi Mataram - Romadonika, Fitri; Baiq Nurul Hidayati; Eka Adithia Pratiwi; Indah Wasliah; Zurriyatun Thoyibah; Henny Yolanda (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
One-third of children in the world experience growth and development disorders, both physical and mental. In Indonesia, around 13–18% of children experience developmental delays, with 16% of them being toddlers who experience neurological and brain development disorders. Children's growth and development are influenced by adequate nutrition, health, and educational stimulation. Early detection and intervention are very important to optimize children's growth and development potential. This community service activity was carried out at TKIT Yarsi Mataram which has around 119 children aged 5–6 years and has not implemented an early detection program for growth and development. Activities include anthropometric examinations (weight, height, head circumference, and arm circumference) and development detection using the Pre-Screening Development Questionnaire (KPSP). The expected results are that each child has a growth and development report card, and teachers receive training in conducting and documenting examinations, so that this early detection program can become a routine activity in schools..